Letter from Max and Georg Bredig to Marianne and Viktor Homburger, March 2, 1941 - Bredig, Max Albert; Bredig, Georg (1941)
Max Bredig (1902-1977) and Georg Bredig (1868-1944) write to Marianne Homburger (1903-1987) and Viktor Homburger (1888-1968), who are currently interned in the Gurs concentration camp in France but expect to be released soon. Max informs them that he has bought ship fares for their trip to the United States and provides updates on friends and family members. Georg Bredig expresses his well-wishes for the family.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Homburger, Viktor, 1888-1968; Gurs (Concentration camp); Emigration and immigration